2017
DOI: 10.1016/j.taap.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune potential of perchloroethylene: Role of lipid-derived aldehydes

Abstract: Tetrachloroethene (perchloroethylene, PCE), an ubiquitous environmental contaminant, has been implicated in inducing autoimmunity/autoimmune diseases (ADs), including systemic lupus erythematosus (SLE) and scleroderma in humans. However, experimental evidence suggesting the potential of PCE in mediating autoimmunity is lacking. This study was, therefore, undertaken to explore PCE’s potential in inducing/exacerbating an autoimmune response. Six-week old female MRL+/+ mice, in groups of 6 each, were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 61 publications
(162 reference statements)
0
3
0
Order By: Relevance
“…Aldehydes found in components of e-cigs are also linked to a higher risk of autoimmune reactions 115 . A murine model demonstrated an increase in autoimmune markers in mice exposed to perchloroethylene in the water at 12, 18 and 24 weeks, including levels of serum ANA (anti-nuclear antibodies), dsDNA (double-stranded DNA) and Scl-70 (scleroderma) antibodies.…”
Section: Oral Lesionsmentioning
confidence: 99%
“…Aldehydes found in components of e-cigs are also linked to a higher risk of autoimmune reactions 115 . A murine model demonstrated an increase in autoimmune markers in mice exposed to perchloroethylene in the water at 12, 18 and 24 weeks, including levels of serum ANA (anti-nuclear antibodies), dsDNA (double-stranded DNA) and Scl-70 (scleroderma) antibodies.…”
Section: Oral Lesionsmentioning
confidence: 99%
“…The same study described how patients exposed to solvents showed more Scl70 antibodies than controls. Even though the biological mechanisms that trigger SSc in a solvent-exposure scenario remain unclear, several studies have suggested its biological plausibility [8,43,44].…”
Section: Solventsmentioning
confidence: 99%
“…Environmental factors have gained much attention in recent years for their role in triggering autoimmunity, with increasing evidence of their influence being apparent from epidemiological and animal studies (39). These factors, including cigarette smoking, crystalline silica, and exposures to trichloroethylene (TCE), perchloroethylene, mercury, pesticides, and pristane are implicated in increasing the risk for ADs (4,4042). Such factors are considered serious threats in the etiology and progression of ADs such as SLE, rheumatic arthritis, systemic sclerosis, and autoimmune hepatitis.…”
Section: Environmental Agents Oxidative Stress and Autoimmunitymentioning
confidence: 99%